Characterization, Antimicrobial Effects, and Cytocompatibility of a Root Canal Sealer Produced by Pozzolan Reaction between Calcium Hydroxide and Silica - Kim, Mi-Ah (Materials (Basel), 2021)
This study aimed to evaluate a newly developed pozzolan-based bioceramic sealer (PZBS) regarding setting time, radiopacity, antibacterial effect, and cytocompatibility. The PZBS was manufactured by mixing calcium hydroxide and silica. The pozzolan reaction was verified by identification of calcium silicate hydrate (C-S-H) using X-ray diffraction analysis. The initial setting time and radiopacity were measured using the ISO 6876/2012 protocol in comparison with other commercially available calcium silicate (CS) sealers. The antibacterial effect of PZBS on biofilms cultured in the bovine root canal was evaluated by measurement of colony-forming units and volume of biofilms in comparison with other calcium hydroxide pastes. The morphological features of the biofilms were observed by scanning electron microscopy (SEM). The cytocompatibility of PZBS was assessed by the viability of bone marrow–derived mesenchymal stem cells and scratch wound healing rate in comparison with other CS sealers. The morphology of the cells cultured on the tested sealers was observed by SEM. The detection of the CS peak confirmed the formation of C-S-H. The initial setting time of PZBS was around 11 h, which was twice as long as the other tested sealers. The radiopacity of PZBS was 4.3 mm/Al, which satisfied the ISO criteria. The antibacterial effect and cytocompatibility of PZBS were comparable to those of the commercially available intracanal medicaments and CS endodontic sealers, respectively. The PZBS has the potential to be used for root canal obturation, and is expected to exert a favorable antibacterial effect.